2013
DOI: 10.1016/j.kjms.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Miniscrew implant applications in contemporary orthodontics

Abstract: The need for orthodontic treatment modalities that provide maximal anchorage control but with minimal patient compliance requirements has led to the development of implant-assisted orthodontics and dentofacial orthopedics. Skeletal anchorage with miniscrew implants has no patient compliance requirements and has been widely incorporated in orthodontic practice. Miniscrew implants are now routinely used as anchorage devices in orthodontic treatment. This review summarizes recent data regarding the interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 35 publications
0
50
0
11
Order By: Relevance
“…Therefore, it is often preferred by orthodontists and patients and has been widely used over the past decade. However, the mini-implant cannot always offer sufficient stability, and the clinical success rate for use of mini-implants has been reported to be approximately 80% 1,2) , with most cases of failure occurring in the posterior region of the mandible 3,4) . Studies also have shown that implant loss occurs most often within 1-2 months after implantation 5,6) , and Moon et al 5) proposed that failure is largely related to characteristics of implantation, including the location.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is often preferred by orthodontists and patients and has been widely used over the past decade. However, the mini-implant cannot always offer sufficient stability, and the clinical success rate for use of mini-implants has been reported to be approximately 80% 1,2) , with most cases of failure occurring in the posterior region of the mandible 3,4) . Studies also have shown that implant loss occurs most often within 1-2 months after implantation 5,6) , and Moon et al 5) proposed that failure is largely related to characteristics of implantation, including the location.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional implantation sites for micro-screws are generally selected between two roots [18] . For the anterior region, micro-screws are generally used to solve problems such as mandibular protrusion and deep lamination.…”
Section: Discussionmentioning
confidence: 99%
“…It was composed of 0.40 mg/L of NaCl, 0.40 mg/L of KCl, 0.80 mg/L of CaCl 2 .H 2 O, 1.0 mg/L of CO(NH 2 ) 2 in distilled water with a pH adjusted and controlled with a 10-N NaOH solution. The performance of any material placed into the oral environment should be assessed with artificial saliva of a known composition, since natural saliva varies widely 22 …”
Section: Methodsmentioning
confidence: 99%